(untitled) (Global Journal of Human-Social Science, 2022)
The proposed Local Sustainability Model (LSM) is framed in the Sustainable Development Goals (SDGs) and focused on Sustainable Cities and Communities. The research is based on the initial praxis developed in the construction of an LSM (Gonzales, 2019) for the Artisanal Gold Mining Activities in southern Peru (AGMA), and is based on the application of the Sustainable Harmonic Movement (SHM) analysis and its integration to methods and techniques such as Canvas, Dolphy, Dynamic Programming, Statistical Validation to determine the sustainability indicators and achieve the measure of Sustainable Development. Finding the LSM implies taking advantage of the natural resource in an efficient and effective way, for which it should be considered to determine the scope limited by the systematized environment (environment), considering in its evaluation the indicators of Environmental, Economic, Social and Governance Sustainability.